Research Progress of Bone Grafting: A Comprehensive Review - Zhang J; Zhang W; Yue W; Qin W; Zhao Y; Xu G (International Journal of Nanomedicine)
Jing Zhang,1,2 Wanhao Zhang,1,2 Wenjie Yue,1,2 Wenhe Qin,1,2 Yantao Zhao,3,4 Gang Xu1,2 1Department of Orthopaedics, First Affiliated Hospital of Dalian Medical University, Dalian, 116011, People’s Republic of China; 2Key Laboratory of Molecular Mechanism for Repair and Remodeling of Orthopaedic Diseases, Dalian, Liaoning Province, 116011, People’s Republic of China; 3Senior Department of Orthopedics, the Fourth Medical Center of PLA General Hospital, Beijing, 100048, People’s Republic of China; 4Beijing Engineering Research Center of Orthopaedic Implants, Beijing, 100048, People’s Republic of ChinaCorrespondence: Yantao Zhao; Gang Xu, Email userzyt@qq.com; xugang@dmu.edu.cnAbstract: Bone tissue, the second most transplanted tissue after blood, is utilized in over 2.2 million bone grafts annually to address various bone-related conditions including fractures, tumors, bone infections, scoliosis, congenital defects, osteoporosis, osteoarthritis, and osteogenesis imperfecta. According to incomplete statistics, $4.3 billion was spent on bone graft materials in 2015 alone, with projections suggesting this figure may reach $66 billion by 2026. The limited availability of autogenous bone graft considered the gold standard due to their three critical biological properties: osteoconduction, osteoinduction, and osteogenesis-alongside the increasing global aging population, may be contributing to this rising expenditure. Furthermore, advancements in biomaterials and engineering technologies have created opportunities for the exploration of new bone graft substitutes. In this review, we will examine the fundamental structure of natural bone and the characteristics of ideal bone graft, highlighting common bone graft materials currently available, such as true bone ceramics, decalcified bone matrix, freeze-dried bone and demineralized freeze-dried bone, bioactive glasses, bone marrow aspirate concentrate, polymer nanocomposites, which have different characteristics in osteogenic, osteoconductivity, osteoinductivity, biocompatibility, mechanical properties, and resorption. How to utilize its advantages to maximize the osteogenic effect will be the focus of this review, and some of the current challenges in the field of bone grafting will be identified, outlining potential directions for future development. In conclusion, the choice of bone graft is critical to bone repair and regeneration, and a comprehensive understanding of the advantages and disadvantages of bone graft materials can improve the effectiveness of related surgical interventions.Keywords: bone graft, true bone ceramics, decalcified bone matrix, freeze-dried bone, bone regeneration